已知\( y = {x^3} + {x^2} \),则\( {y^{(3)}} = 6 \)( ).
举一反三
- 应用Matlab软件计算行列式[img=110x88]17da5d7b00219d6.png[/img]为( ). A: x^2 - 6*x^2*y^2 + 8*x*y^3 - 3*y^4 B: x^3 - 6*x^2*y^2 + 8*x*y^3 - 3*y^4 C: x^4 - 6*x^2*y^2 + 8*x*y^3 - 3*y^4 D: x^5- 6*x^2*y^2 + 8*x*y^3 - 3*y^4
- 已知\( y = {x^3} + 2x \),则\( y'' \)为( ). A: \( 3{x^2} \) B: \( 6x \) C: 6 D: 0
- 已知|x|=3,|y|=2,且x>y,则yx=()。
- 已知x=1,y=2,z=3,执行下列语句if(x>y) z=x;x=y;y=z;则x,y,z的值分别是 A: x=1,y=2,z=3 B: x=2,y=3,z=1 C: x=2,y=2,z=1 D: x=2,y=3,z=3
- 已知\( y = 2{x^3} + 7x + \ln 3 \),则\( {y^{(3)}} \)为 。______